Polyphenol content and antioxidant capacity in organically and conventionally grown vegetables - Unal, Kevser; Darnis, Deny Susanti; Bakhtiar, M. Taher (Coastal Life Medicine Media co., Limited, 2014)
Objective: To evaluate the polyphenol content and antioxidant capacity of ethanol some organically and conventionally grown leafy vegetables. extracts of Methods: The ethanol extracts of kailan (Brassica alboglabra), bayam (Amaranthus spp.) and sawi (Brassica parachinensis) were tested for total phenolic content (TPC), total flavonoid content (uTsFiCn)g, and total anthocyanin content (TAC) and the antioxidant capacity of the extracts measured 2,2-diphenyl-1-picrylhydrazyl assay. Results: In TPC test, sawi extract showed the highest phenolic content while bayam contained tohrgea lneiacsatl lpyh gernoowlnic scaownit eenxtt rafocrt bshoothw eodrg tahnei chailglhy easnt dfl acvoonnvoeindt icoonnatlelny t,g rwohwinle toyrpgeasn. iIcna lTlyF Cg rtoewstn, ckoaniltaenn te xotfr athcet schoonwveedn titohnea llelya sgt rfolwavno ntyopide sc oonf tveengte atambolen ge xatlrl atcytpse ws aosf tvheeg ehtiagbhleesst. Tinh ek afllaiavno naonidd itnhcer eleaassetd iwn itsha wthi.e Fionrc r2e,a2s-idnigp hcoenncyel-nt1r-aptiiocnr yolfh yedacrahz yelx trraadcitc. aAl lls ccaovnevnegnitniogn aaclltyi vgirtyo,w tnh ev eagcettiavbitlye extracts showed higher antioxidant activity compared to their organically grown counterparts. cEoxntrvaecnttsi oonfa lcloyn gvreonwtnio knaailllayn g arnodw no rsgaawniic sahlloyw gerdow tnh es ahwigi.h est percentage inhibition followed by There were no correlation between TPC, TcFoCrr,e TlaAtCio ann bde ItCw2e5 eonf both organically and conventionally grown vegetables. However, there was a relatively similar poTlyApCh aenndo l ICco25n otfe ncto nbveetnwteioenna ollryg agnroicwanll yv eagnedta bcloen veexntrtaiocntsa. lTlyh eg rroewsunl tvse sgheotawbelde aecxttirvaicttys .c Homowpaerveedr, ttoh teh ceo onrvgeanntiicoanlalyll yg rgorwonw ne xvteragcettsa.bles extracts generally have higher antioxidant Conclusions: These results suggested that the different types of agricultural practice had a significant contribution to the polyphenol content and antioxidant activity in the vegetables.